2008
DOI: 10.4049/jimmunol.180.5.2942
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Secretory and Endosomal Compartments in Presentation of an Exogenous Self-Glycolipid to Type II NKT Cells

Abstract: Natural Killer T (NKT) cells recognize both self and foreign lipid Ags presented by CD1 molecules. Although presentation of the marine sponge-derived lipid αGalCer to type I NKT cells has been well studied, little is known about self-glycolipid presentation to either type I or type II NKT cells. Here we have investigated presentation of the self-glycolipid sulfatide to a type II NKT cell that specifically recognizes a single species of sulfatide, namely lyso-sulfatide but not other sulfatides containing additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
64
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 58 publications
8
64
0
Order By: Relevance
“…Two findings are consistent: (i) cells stained with tetramers loaded with an immunodominant synthetic cis-tetracosenoyl sulfatide also are predominantly Vβ8 + , Vα3 + , and Vβ3 + (Fig. S4); and (ii) antigen fine specificity of a sulfatide-reactive hybridoma, Hy19.3, showed that it is only strongly reactive to lyso-sulfatide (17,18,29) and utilizes the TCR Vα1-Jα26 and Vβ16-Jβ2.1 gene segments with similar CDR1α, CDR3α, and CDR2β sequences to the TCRs of sulfatide/CD1d-tetramer + cells (Fig. S5).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Two findings are consistent: (i) cells stained with tetramers loaded with an immunodominant synthetic cis-tetracosenoyl sulfatide also are predominantly Vβ8 + , Vα3 + , and Vβ3 + (Fig. S4); and (ii) antigen fine specificity of a sulfatide-reactive hybridoma, Hy19.3, showed that it is only strongly reactive to lyso-sulfatide (17,18,29) and utilizes the TCR Vα1-Jα26 and Vβ16-Jβ2.1 gene segments with similar CDR1α, CDR3α, and CDR2β sequences to the TCRs of sulfatide/CD1d-tetramer + cells (Fig. S5).…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with this idea, a number of CD1d-reactive T cell hybrids isolated from MHC class II-deficient mice (15,16,28) are Vα3 + , Vα8 + , and Vα4 + and do not show any reactivity to sulfatide (17,18). Accordingly, none of them expressed the TCR Vα-Jα and Vβ-Jβ gene segments predominantly used by sulfatide/CD1d-tetramer + cells.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, sulphatide with a nervonoyl acyl chain forms stable complexes with human CD1a and CD1d and mouse CD1d and preferentially stimulates sulphatide-specific human T-cell clones [17] (and our unpublished results) and a mouse T-cell hybridoma [18]. Lysosulphatide can also form stimulatory complexes with CD1d and activate- specific T cells [19]. CD1d-lysosulphatide complexes are probably formed in a pre-lysosomal compartment and do not require egression from the ER of newly synthesized CD1d molecules [19].…”
Section: Structure Of Exogenous and Self-lipid Antigenssupporting
confidence: 58%
“…Lysosulphatide can also form stimulatory complexes with CD1d and activate- specific T cells [19]. CD1d-lysosulphatide complexes are probably formed in a pre-lysosomal compartment and do not require egression from the ER of newly synthesized CD1d molecules [19]. Recently, lysophosphatidylcholine has been found to stimulate human CD1d-restricted type II NKT cells [20].…”
Section: Structure Of Exogenous and Self-lipid Antigensmentioning
confidence: 99%